2022
DOI: 10.3390/en15239225
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Energy as a Megatrend of Audit of Investment Processes of the Energy Complex

Abstract: The global trend is constantly increasing investments in strategic sectors of the economy, for example the electric power industry, which, in many countries, is becoming diversified and dispersed due to the multitude of entities investing in energy production and renewable resources, which leads to an increase in the heterogeneity of investment decisions. There is an urgent need to control the movement of investments, budget funds, as well as their development in the process of implementing investment programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In these conditions, mutual settlements of all consumers belonging to the same group pay the "boiler holder" for electricity transmission services at a single (boiler) tariff. Due to this, the "boiler holder" collects the necessary gross revenue of the network organizations included in the "boiler" and distributes it among adjacent network organizations through the use of individual tariffs, thereby ensuring the necessary volume of production, revenue and the corresponding share of profit of each of the network organizations required to cover their production costs [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…In these conditions, mutual settlements of all consumers belonging to the same group pay the "boiler holder" for electricity transmission services at a single (boiler) tariff. Due to this, the "boiler holder" collects the necessary gross revenue of the network organizations included in the "boiler" and distributes it among adjacent network organizations through the use of individual tariffs, thereby ensuring the necessary volume of production, revenue and the corresponding share of profit of each of the network organizations required to cover their production costs [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Gryzunova has suggested that the approach to investment projects in the field of green energy must strike a balance between consumer demand and the feasibility of providing specialized installations [ 28 ]. Through their study in China regarding green public procurement, Zhang and Jiang found that they stimulate companies to pay attention to the types of energy they use in the production process [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Gryzunova, state governments establish development strategies in order to reduce costs, increase investments in the use of renewable energy sources. Russia's target scenario is for investments in this field to represent, in the period 2022–2030, 1% of GDP [ 28 ]. Lyu et al asserted that France has proposed, by law, to be zero GHG by 2050, giving up electricity generated with gas and coal [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, all the investments needed to reach that balance by the end of the planning horizon are optimally distributed across the planning period, so that the total surplus is maximized. The MARKALbased framework was widely utilized to assess developmental directions and the velocity of technological transition mainly for the energy sector, also towards its decarbonization, in Canada [28,29], Switzerland [30], Malaysia [31], Russia [32], the UK [33][34][35][36], the USA [37,38], Austria [39], China [40][41][42][43], Portugal [44][45][46], Italy [47], Iran [48], Turkey [49], Kazakhstan [50], Ireland [51], Poland [52], Greece [53], and Bulgaria [39].…”
Section: Markal-an Overviewmentioning
confidence: 99%